Between Two Fires: Torture and Displacement in Northern Uganda - Odongyoo, Francis; Lamony, Stephen (USA : Witness, 2006)
The ongoing civil war in Northern Uganda has created an unprecedented humanitarian crisis and regional instability. While the LRA has committed war crimes against the displaced population, including the abduction of some twenty thousand children, the Ugandan People's Defence Forces (UPDF) who were mobilized to protect civilians have also committed human rights violations including arbitrary detention, torture and rape.
Keywords: Documentary films